Digging for words : José Alberto Gutiérrez and the library he built - Kunkel, Angela Burke (Schwartz & Wade Books, an imprint of Random House Children's Books, 2020)
In Bogotá, Columbia, young José eagerly anticipates Saturday, when he can visit the library started by José Alberto Gutiérrez, a garbage collector, and take a book home to enjoy all week. Includes note about Gutiérrez's life and Bogotá.